2019
DOI: 10.1111/jdv.15983
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between patients’ characteristics and prescribed systemic treatments for psoriasis: a semantic connectivity map analysis of the Swiss Dermatology Network for Targeted Therapies registry

Abstract: Background Several treatment options are currently available for the treatment of psoriasis. Objective To explore the main associations between patients’ characteristics and systemic treatments prescribed for psoriasis in a large group of patients observed in real‐life clinical practice. Methods This was a retrospective analysis of baseline data collected within the Swiss Dermatology Network for Targeted Therapies registry in Switzerland between March 2011 and December 2017. Semantic map analysis was used in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Associations among patients' demographics, clinical characteristics and survival were explored using semantic map analysis (4)(5)(6)(7). This is a data-mining algorithm that is able to find and display the most important associations between different variables, taking into account the effect of other covariates in the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations among patients' demographics, clinical characteristics and survival were explored using semantic map analysis (4)(5)(6)(7). This is a data-mining algorithm that is able to find and display the most important associations between different variables, taking into account the effect of other covariates in the system.…”
Section: Discussionmentioning
confidence: 99%
“…Different algorithms have been developed with the aim of exploring the multidimensional complex interactions among variables in databases. Among these, a datamining algorithm, called semantic map analysis, which is able to show the most important connections between variables in a dataset, has been used in the context of different skin conditions, including chronic hand eczema, psoriasis, hidradenitis suppurativa and associations of vascular endothelial growth factor with MM patients' characteristics and survival (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…We did not find any study on PsA that examined the relationship between BMI and response to secukinumab. A Swiss registry (38) showed that secukinumab was prescribed more often to overweight psoriasis patients. In contrast to our results, a pooled data analysis from phase 3 secukinumab psoriasis trials (39) found that the BMI decreased as the response rate increased.…”
Section: Discussionmentioning
confidence: 99%
“…The Swiss Dermatological Network for Targeted Therapies (SDNTT) is the national psoriasis registry that includes adults with moderate-to-severe psoriasis who are starting a new systemic psoriasis therapy that they have not previously used. 2,6,20,22,[32][33][34] All participants gave their signed informed consent and could follow the study instructions in German, French, Italian or English. The data collection of the registry follows the European consensus of the Network of Registries for Systemic Psoriasis Therapies (PSONET).…”
Section: Patient Population and Data Collectionmentioning
confidence: 99%